Food consumption and adipose tissue DDT levels in Mexican women - Galván-Portillo Marcia; Jiménez-Gutiérrez Carlos; Torres-Sánchez Luisa; López-Carrillo Lizbeth (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
This article analyzes food consumption in relation to levels of DDE (the principal metabolite of DDT) in the adipose tissue of 207 Mexican women residing in States with high and low exposure to DDT. Data on the women's dietary habits and childbearing history were obtained from a personal interview. Adipose tissue DDE levels were measured by gas-liquid chromatography and compared by analysis of variance (ANOVA) and multiple linear regression. Adipose tissue DDE levels increased significantly with age (p = 0.005) and residence in coastal areas (p = 0.002) and non-significantly with the consumption of onion, cauliflower, prickly pear, squash blossoms, sweet corn, broad beans, chili pepper sauce, ham, and fish. Even so, during breastfeeding there was a non-significant reduction in these levels. The findings suggest that certain foods serve as vehicles for DDE residues and confirm that breastfeeding is a mechanism for the elimination of this insecticide, which accumulates over the years in the human body.